The Influence of Lighting on The Bedroom Towards The Sleep Quality of Children Aged 0-5 Years - Uding, Risnawati; Fianti, Fianti; Yulianti, Ian (Physics Communication, 2024)
Lighting in the bedroom is important in maintaining the quality of children's sleep. At the age of 0-5 years, a child has a sleep duration of around 11-18 hours, so it is necessary to pay attention to the lighting in the bedroom so that children have quality sleep time. This study aims to determine the effect of lighting in the bedroom on the sleep quality of children aged 0-5 years. Samples were taken randomly with the age range of children 0-5 years with the criteria of children accustomed to sleeping with the lights off as many as 6 samples.  The number of samples was adjusted to the availability of samples around the research site in Tinjomoyo village. Data collection techniques were observation and questionnaires. The parents of the sample filled out the observation sheets and questionnaires. The duration of data collection depends on how many times each sample wakes up during sleep at night, starting when the child falls asleep until 03.00 AM. The results showed that there was an effect of bedroom lighting on the sleep quality of children aged 0-5 years as indicated by a change in the child's total awakening, which is an average of 2 fewer awakenings during sleep from the lights on to the lights off.